Emiliano Zapata ou la photographie au service de la construction d’une icône - Marion Gautreau (Caravelle)
By studying the figure of Emiliano Zapata, this article recounts the trajectory which converted a Revolutionary often considered by the ruling classes as a bandit into a hero, and later into an icon. Through the analysis of the publication of Zapata’s photographs in the Mexican illustrated press and the study of some specific portraits, we try to decode the double iconic process: the historical figure and the one in the portraits.